Компьютерные технологии мультифизических процессов - Назаренко, Сергей Александрович (ЛІРА, 2016)
В докладе описаны формализованные на единой комплексной научно-методологической базе компьютерные технологии мультифизических процессов. Основополагающим компонентом анализа мультифизических проблем является построение связанных моделей. Приведены примеры реализованных разработок физико-механических процессов.

The rapid development of CAD/CAM/CAE/CIM/PLM systems is a worldwide trend. The research includes a brief summary of main scientific results of multidisciplinary modeling of loaded structures and technological systems. The basic component analyses of multiphysics problems are to build related models. Examples of implemented applications of physical and mechanical processes in the manufacture are presented.
Keywords: компьютерные технологии; физические процессы; связанные модели; technological systems; multiphysics; supercomputer simulation based design